Pengaruh Laba Bersih, Potensi Pertumbuhan dan Arus Kas Operasi Terhadap Dividen Payout Ratio Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia - Yunina, Yunina (Universitas Malikussaleh, 2013)
This research is aimed to analyze the influence of net income, growth potential and operating cash flow to dividend payout ratio onÂ manufacturing companies that were listed in Indonesian stock exchange. The method used is multiple linier regression with SPSS, 17.0. The result shows that net income, growth potential and operating cash flow simultaneously are significant to dividend payout ratio. The influence reaches 8,9%. The results of analisyst using t-test indicate that partially, there is a significant influence between net income and growth potential with dividend ratio. While operating cash flow, partially there is not a significant influence with dividend payout ratio.